2004
DOI: 10.1097/01.asn.0000130154.42061.c6
|View full text |Cite
|
Sign up to set email alerts
|

Increased Infarct Size in Uremic Rats

Abstract: Abstract. In patients with renal failure, myocardial infarction (MI) is more frequent and the rate of death from acute MI is very high. It has been argued that ischemia tolerance of the heart is reduced in uremia, but direct evidence for this hypothesis has not been provided. It was the purpose of this study (1) to ligate the left coronary artery and to measure the nonperfused area (risk area: total infarction plus penumbra) as well as the area of total infarction in subtotally nephrectomized (SNX) rats compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
74
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(82 citation statements)
references
References 38 publications
6
74
1
1
Order By: Relevance
“…Inadequate capillary density will restrict the ability of the heart to cope with increased oxygen demand. Finally, after ligation of the left coronary, infarcts are larger in animals with experimental uremia, pointing to reduced ischemia tolerance (31).…”
Section: Cardiac Fibrosis and Microvessel Diseasementioning
confidence: 99%
“…Inadequate capillary density will restrict the ability of the heart to cope with increased oxygen demand. Finally, after ligation of the left coronary, infarcts are larger in animals with experimental uremia, pointing to reduced ischemia tolerance (31).…”
Section: Cardiac Fibrosis and Microvessel Diseasementioning
confidence: 99%
“…92,93 Previous work on IRI demonstrated that cell death occurs through necrosis and apoptosis and that inhibiting apoptosis during reperfusion significantly improves outcomes. 94 -96 Cardiomyocyte apoptosis also plays a causal role in the development of uremic 97 and nonuremic heart failure, whereas inhibiting apoptosis reduces cardiac dysfunction in heart failure.…”
Section: Apoptosismentioning
confidence: 99%
“…described to restrict compensatory vasodilation and the ability of the heart to cope with increased oxygen demand (17). This might have been of special importance in the presence of PF4-H-Abs, which are known to induce platelet activation (6) and to act via the F(ab)2 fragment of IgG PF4-H-ABs binding to and activating microvascular endothelial cells (18), thereby potentially aggravating the already impaired cardiac perfusion and promoting cardiac fibrosis.…”
Section: Discussionmentioning
confidence: 99%